Substrate Integrated Waveguide Antenna with Metasurface for Cube Satellites - An, Hyungjun; Kim, Changseong; Park, Yong Bae (ICTC 2019 - 10th International Conference on ICT Convergence: ICT Convergence Leading the Autonomous Future, 2019)
In this paper, the substrate integrated waveguide (SIW) slot array antenna using metasurface for cube satellite operating in the C-band was simulated. The antenna is sandwiched structure arranging a 2 × 5 periodic square conductor patch on the substrate integrated waveguide. As the surface wave excited in the SIW slot array propagates on the metasurface, additional resonance occurred and the impedance matching was better than the conventional antenna. The overall size of the final antenna was {6.75cm× 2.35cm× 0.37 cm} (1.07λ-{0}× 0.37λ-{0}× 0.06λ-{0} at 4.74 GHz). The simulated results have a bandwidth of 4.73-4.87 GHz (3.38%) satisfying the condition of |S11|<-10dB. The maximum realization gain is 6.58 dB at 4.76 GHz.
Keywords: C-bands; Metasurface; Sandwiched structure; Simulated results; Slot array antennas; Slot arrays; C-Band; Cube Satellite; Metasurface; Satellite antenna; SIW antenna